Personality Traits and The Level of Job Satisfaction and Burnout Syndrome Among Healthcare Employees - Monika PRZYMUS; Sylwia GOLAB; Beata BEDZIK (Communications of International Proceedings, 2024)
The study aimed to assess the relationship between personality traits and job satisfaction as well as burnout syndrome among healthcare employees. The focus was on psychological aspects relating to the five-factor model of personality, describing dimensions such as neuroticism, extraversion, openness to experience, agreeableness, and conscientiousness, which can affect job satisfaction and risk of burnout. This issue is of public health significance as low job satisfaction and high burnout among healthcare workers affect patient care quality and employment stability. A sample of 120 female nurses was surveyed, covering various positions, using the Job Satisfaction Scale (SSP), the Oldenburg Burnout Inventor (OLBI), and the NEO-FFI personality inventory. Correlation and multiple regression analyses were applied to identify statistically significant relationships. Results indicated limited predictive power of personality traits on job satisfaction and burnout levels. However, higher satisfaction was associated with lower burnout, specifically regarding exhaustion and disengagement.
Keywords: Job satisfaction; job burnout; personality; employee turnover; nurses